2022
DOI: 10.3390/s22207873
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sheet Thickness and Excitation Frequency on Hysteresis Loops of Non-Oriented Electrical Steel

Abstract: The paper focuses on modeling the rate dependence of hysteresis loops in conductive magnetic materials. The concept, which was advanced about fifty years ago by Chua, is discussed. It is shown that the viscous-type equation considered by Zirka and co-workers belongs to the class of Chua-type models. The dynamic effects are described with a simple fractional power law. The value of the exponent in the above-mentioned power law may be assessed on the basis of measurements of coercive field strength at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The present paper is a follow up of previous research devoted to modeling hysteresis curves under an increased excitation frequency [1]. The aim of the paper is to demonstrate the usefulness of a viscous-type equation, considered previously by Zirka et al [2], as a means to describe the so-called excess field component.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The present paper is a follow up of previous research devoted to modeling hysteresis curves under an increased excitation frequency [1]. The aim of the paper is to demonstrate the usefulness of a viscous-type equation, considered previously by Zirka et al [2], as a means to describe the so-called excess field component.…”
Section: Introductionmentioning
confidence: 71%
“…The issue of loss separation in soft magnetic materials may be tackled from different perspectives, and a recent review on the subject can be found in [1]. Here, we follow the so-called two-term separation scheme, in which field strength at an increased excitation frequency is computed from…”
Section: The Viscous-type Equationmentioning
confidence: 99%
See 3 more Smart Citations